Poster: You Driving? Talk to You Later - Kansal, Aman; Bahl, Victor (Mobisys 2011: The Ninth International Conference on Mobile Systems, Applications, and Services. (BEST POSTER AWARD), 2011)
We present a phone based sensing system, referred to as driver detection system (DDS), to determine if a user in a moving vehicle is a driver or a passenger. We realize this goal using various user micro-movements that can be detected using just the mobile phone sensors without relying on additional wearable sensors or custom instrumentation in the vehicle. The detection is based on inferring which part of the vehicle the user is present in, such as passenger side vs. driver side or front vs. rear, as well as some key activities performed by the driver. We foresee several useful applications for the DDS including, delivery of notifications (e.g., voice calls, emails, ads, etc.) based on availability of user attention, feeding the detection results into systems to compute commuting carbon footprints or for tracking reckless driving behavior, etc.